Answer:
Step-by-step explanation:
(0, -9) and (3,3)
(3+9)/(3-0) = 12/3 = 4
y + 9 = 4(x - 0)
y + 9 = 4x - 0
y = 4x - 9
Answer:
S6tep-by-step explanation:
4^(11+8) = 4^19 is the solution
Answer:
(-16, 0) and (0,-12) are exactly two points on the graph of the given equation.
Step-by-step explanation:
Here, the given expression is : ![M(a) = -\frac{3}{4} a-12](https://tex.z-dn.net/?f=M%28a%29%20%3D%20-%5Cfrac%7B3%7D%7B4%7D%20a-12)
Here, let M(a) = b
⇒The equation becomes ![b = -\frac{3}{4} a-12](https://tex.z-dn.net/?f=b%20%3D%20-%5Cfrac%7B3%7D%7B4%7D%20a-12)
Now, check for all the given points for (a,b)
<u>1) FOR (-9,0)</u>
![RHS is -\frac{3}{4} (-9)-12 = -5.25 \neq 0](https://tex.z-dn.net/?f=RHS%20%20is%20%20-%5Cfrac%7B3%7D%7B4%7D%20%28-9%29-12%20%20%3D%20%20%20-5.25%20%5Cneq%200)
Hence, (-9,0) is NOT on the graph.
<u>2) FOR (-16,0)</u>
Here, LHS = b = 0
and![RHS = -\frac{3}{4} (-16)-12 = 12-12 = 0](https://tex.z-dn.net/?f=RHS%20%20%3D%20%20%20-%5Cfrac%7B3%7D%7B4%7D%20%28-16%29-12%20%20%3D%2012-12%20%20%3D%200)
Hence, LHS = RHS = 0 So, (-16,0) is on the graph.
<u>3) FOR (0,12)</u>
Here, LHS = b = 12
![RHS is -\frac{3}{4} (0)-12 = -12 \neq 12](https://tex.z-dn.net/?f=RHS%20%20is%20%20-%5Cfrac%7B3%7D%7B4%7D%20%280%29-12%20%20%3D%20%20%20-12%20%20%5Cneq%2012)
Hence, (0,12) is NOT on the graph.
<u>4) FOR (0,-12)</u>
Here, LHS = b = -12
![RHS is -\frac{3}{4} (0)-12 = -12](https://tex.z-dn.net/?f=RHS%20%20is%20%20-%5Cfrac%7B3%7D%7B4%7D%20%280%29-12%20%20%3D%20%20%20-12%20)
and LHS = RHS = -12
Hence, (0,-12) is on the graph.
Hence, (-16, 0) and (0,-12) are exactly two points on the graph of the given equation.